2023
DOI: 10.1007/s40615-023-01665-8
|View full text |Cite
|
Sign up to set email alerts
|

Resident Versus Attending Prenatal Care Models: an Analysis of the Effects of Race and Insurance on Appointment Attendance

Abstract: Objective To describe patient differences by prenatal care (PNC) model and identify factors that interact with race to predict more attended prenatal appointments, a key component of PNC adherence. Methods This retrospective cohort study used administrative data targeting prenatal patient utilization from two OB clinics with different care models (resident vs. attending OB) from within one large midwestern healthcare system. All appointment data among pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…Rather, differential levels of resources for various hospital-based clinics may contribute to this disparity. While this study did not investigate specific reasons for prolonged follow-up, previous studies have found that patients in resident OB/GYN practices cited inconvenient appointment availability and longer times spent waiting prior to seeing a provider as reasons to cancel appointments 14,19 . Beyond gynecologic settings, Medicaid-insured patients have been widely shown to face longer waiting room times than privately insured patients 20 .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Rather, differential levels of resources for various hospital-based clinics may contribute to this disparity. While this study did not investigate specific reasons for prolonged follow-up, previous studies have found that patients in resident OB/GYN practices cited inconvenient appointment availability and longer times spent waiting prior to seeing a provider as reasons to cancel appointments 14,19 . Beyond gynecologic settings, Medicaid-insured patients have been widely shown to face longer waiting room times than privately insured patients 20 .…”
Section: Discussionmentioning
confidence: 91%
“…While this study did not investigate specific reasons for prolonged follow-up, previous studies have found that patients in resident OB/GYN practices cited inconvenient appointment availability and longer times spent waiting prior to seeing a provider as reasons to cancel appointments. 14,19 Beyond gynecologic settings, Medicaid-insured patients have been widely shown to face longer waiting room times than privately insured patients. 20 However, the presented findings suggest that canceled appointments cannot fully explain the delay, as intervals to first scheduled colposcopy remained significantly longer among the resident practice group regardless of cancelations.…”
Section: Discussionmentioning
confidence: 99%